IMPROVEMENT OF EXPANSIVE SOIL BY ELECTRO-KINETIC METHOD - Tran Thi Thanh Thuy; Doni Prakasa Eka Putra; Wawan Budianta; Hemanta Hazarika (Geological Engineering Department Universitas Gadjah Mada, 2015)
The roadway in Karangjati, Ngawi Regency, East Java, Indonesia, which is underlain by expansive soil, is susceptible to damage due to volume change. This research aims to improve the engineering properties, such as consistency limits, compressibility, and undrained shear strength of the montmorillonite dominated soil in this area using an electrokinetic stabilization method. Four electro-kinetic experiments were conducted using different electrolytes (calcium chloride or pure water) under different conditions (no-flow or flow water). The results show that, pH values of all soil samples decreased at anolyte and increased at catholyte. Atterberg limits of the soil samples were found to increase, where the liquid limit (LL) range of 79.72– 86.14%, plastic limit (PL) 25.22–30.80%, and plasticity index (PI) 53.28–60.92, liquidity Index (LI) 0.91–1.08. The compression index Cc was 0.50– 0.742. Undrained shear strength of treated soil range of 7–11 kPa. Moreover, strengthening degree of the treated soils achieve 304–556%. The soil improvement was achieved by decreasing the Atterberg limits, and compressibility and increasing the undrained shear strength. Applying calcium chloride and flow water condition were the most effective methods for the soil improvement. The mineralogical compositions of the soil samples did not change after the treatment. Keywords: Electro-kinetic stabilization, electro chemical injection, clayey soil improvement.